MAPPING THE GULF STATES WITHIN THE GLOBAL COMPETITION LAW FRAMEWORK (EU and comparative law issues and challenges series (ECLIC), 2024)
The Gulf Cooperation Council (GCC) countries are part of the 130 jurisdictions worldwide that have enacted competition laws. The competition law frameworks in the Gulf States are primarily influenced by European Union (EU) competition law, U.S. antitrust, international organizations, etc. However, these jurisdictions possess distinct, sui generis characteristics, as directly transplanting the entire acquis from these systems would be impractical. The Gulf region’s unique historical, cultural, and political contexts have significantly influenced the development of these legal frameworks. As these countries strive to implement diversification strategies to reduce oil reliance, competition laws have emerged as essential tools for promoting competition, enhancing market efficiency, fostering economic growth, ensuring fairness, protecting consumer welfare, and, sometimes, encouraging innovation. Some member states of the Gulf have more inclusive and revised competition law toolboxes in the region than others. However, they all address the goals, key pillars, and well-established institutional frameworks.